Dog man : Lord of the fleas - Pilkey, Dav, 1966-; Garibaldi, Jose. (New York, NY : Graphix, An Imprint of Scholastic, 2018)
When a new bunch of baddies bust up the town, Dog Man is called into action -- and this time he isn't alone. With a cute kitten and a remarkable robot by his side, our heroes must save the day by joining forces with an unlikely ally: Petey, the World's Most Evil Cat. But can the villainous Petey avoid vengeance and venture into virtue?
Keywords: Dog Man (Fictitious character -- Juvenile fiction; Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Dogs -- Comic books, strips, etc; Dogs -- Juvenile fiction; Police -- Comic books, strips, etc; Police -- Juvenile fiction; Cartoons and comics; Dogs -- Fiction; Graphic novels; Comic books, strips, etc; United States; Graphic novels; Graphic novels; Humorous comics